The effect of warm-up modalities on trampoline flight time performance - Harden, M.; Earnest, C. P. (Central European Journal of Sport Sciences and Medicine, 2015)
Trampoline flight time is a recent addition to Olympic scoring and was sufficient in weight to displace a formed medal winner from a podium placement at the 2012 Olympics. The aim of our study was to examine different warm-up routines on trampoline flight time. We examined ten elite, female trampolinists (mean ± SD: age 19.2 ±5.4 y) who performed six different warm-up routines in a randomised, cross-over, counter-balanced manner: (a) static stretching (STAT, control), (b) STAT+10 trampoline bounces, (c) dynamic stretching (DYN), (d) DYN+10 trampoline bounces, (e) DYN+Drop jumps (DYN+DJ) and (f) DYN+isometric mid-thigh pulls (DYN+IP). Data were analysed using general linear models, Dunnett-HSU post-hoc tests vs. Control/STAT and magnitude based inferences vs. control. Our analysis demonstrated that total flight time following DYN 10 (17.29 ±0.52s, 83% likely beneficial, P < 0.002) was significantly longer versus STAT (16.59 ±0.49 s), with a trend toward significance for DYN (16.97 ±0.20 s; 22% likely beneficial, P = 0.077). The DYN-IP (14.04 ± 0.48 s) and DYN-DJ (14.15 ±0.66 s) produced the shortest vs. all warm-up forms (P < 0.005). To the contrary, the DYN+DJ and DYN+IP conditions were >99% likely to be detrimental to performance. Our results demonstrate a clear improvement in flight times when using a dynamic warm-up coupled with a trampoline specific bouncing task (DYN+10).